Field Investigation on Thermal Regime of Permafrost and Talik in a River Terrace, the Interior of Qinghai-Tibet Plateau - Yunzhi Zhang; Furong Liu; Xingbing Wang; Pengfei He; Jinggang Cui; Yishan Wang; Yanhu Mu (Geofluids)
To carry out engineering construction in a permafrost area, it is of great importance to grasp the spatial distribution of permafrost and its hydrothermal characteristics within the scope of engineering activities. Compared with the continuous permafrost area, the permafrost distribution in discontinuous permafrost area is complicated due to existence of island talik, which causes highly poor continuity and uniformity of ground hydrothermal conditions and brings great difficulty and uncertainty to the engineering geological investigation. In the present study, the spatial distribution of permafrost and the freeze-thaw process of shallow ground at the I-stage terrace of a river on the Qinghai-Tibet Plateau were studied based on field investigation including drilling, electrical resistivity tomography, and borehole temperature measurement. The results show that the relict permafrost, patchy permafrost, and island talik are distributed in the limited range of the study area. Among them, the buried depth of relict permafrost layer is in the range of 7 ~ 14 m, while the patchy permafrost layer is in the range of 3.0 ~ 17.0 m depth, and the mean annual ground temperature of both is close to -0.1°C, which belongs to extremely high-temperature permafrost. The seasonal freezing/thawing depths of shallow ground within the relict permafrost, patchy permafrost, and island talik range from 2.5 to 3.0 m. The freezing period of the seasonal freezing layer is 5.5 months, while the thawing period of the seasonal thawing layer is 6 months. The complex plane and spatial distribution of permafrost in the field are closely related to local factors such as topography, geomorphology, groundwater, and lithology of shallow ground. It is believed that the formation of the island talik in the study area is controlled by solar radiation and precipitation infiltration.